Laboratory Screening of Control Agents Against Isolated Fungal Pathogens Causing Postharvest Diseases of Pitaya in Guizhou, China - Li, Yong; Chen, Haijiang; Ma, Lan; An, Youshan; Wang, Hui; Wu, Wenneng (Frontiers in Chemistry, 2022)
Pitaya, or dragon fruit, is a typical tropical fruit with appealing taste and diverse health benefits to human. Plantation of pitaya in Guizhou Province in China has greatly boost the income of local farmers and alleviate poverty. However, frequent occurrence of postharvest diseases has brought large economic loss. To find a solution, we set out to identify the postharvest diseases-causing agents of Guizhou pitaya. Several fungi were isolated from diseased pitaya and identified to species based on ITS1 sequence similarity. Of them, Penicillium spinulosum, Phoma herbarum, Nemania bipapillata and Aspergillus oryzae were for the first time found to cause dragon fruit disease. In consideration of their prevalence in postharvest fruit diseases, A. alternata H8 and F. proliferatum H4 were chosen as representative pathogens for drug susceptibility test. Among the tested drugs and plant extracts, 430 g/L tebuconazole and 45% prochloraz, were found to be the most potent fungicides against H8 and H4 respectively. The research provides insights on mechanism and control of postharvest diseases of dragon fruits in Guizhou China and thus could be of economic and social significance to local farmers and government.